Revitalizing Tarekat Values in Islamic Character Education in the Digital Age - Ulfa Maskanah; M Mujib (Journal of Research and Thought on Islamic Education (JRTIE), 2025)
This study aims to explore and revive the values of tarekat in Islamic character education that are relevant and contextual in the digital age. Amidst the rapid development of information technology, character education faces increasingly complex challenges, such as the rise of cyberbullying, digital copyright infringement, the spread of hoaxes, and a decline in ethics and morals in online interactions. This shows that an educational approach that only emphasizes cognitive aspects is no longer adequate. An approach that can instill spiritual and moral values deeply is needed. This study uses a descriptive qualitative method through a literature review, analyzing various works that discuss Sufi values and their relevance to contemporary Islamic education. This study shows that Sufi values, such as zuhud, wara', sabar, ridha, and tawakal, have a strong influence in shaping an honest, disciplined, humble, and resilient religious character. The revitalization of these values can be achieved by integrating them into the Islamic education curriculum, strengthening the role of teachers as spiritual guides, digitizing Sufi teachings to make them easily accessible to the digital generation, and establishing virtual communities that prioritize Sufi values. Another important strategy is collaboration with Muslim influencers who have credibility and commitment to these values, to convey moral messages creatively and communicatively to the younger generation. This research is expected to make a real contribution to the development of a spiritual, relevant, and dynamic Islamic character education model that is capable of facing the challenges of the digital age